2018
DOI: 10.3389/fimmu.2018.02954
|View full text |Cite
|
Sign up to set email alerts
|

mPGES-1-Mediated Production of PGE2 and EP4 Receptor Sensing Regulate T Cell Colonic Inflammation

Abstract: PGE2 is a lipid mediator of the initiation and resolution phases of inflammation, as well as a regulator of immune system responses to inflammatory events. PGE2 is produced and sensed by T cells, and autocrine or paracrine PGE2 can affect T cell phenotype and function. In this study, we use a T cell-dependent model of colitis to evaluate the role of PGE2 on pathological outcome and T-cell phenotypes. CD4+ T effector cells either deficient in mPGES-1 or the PGE2 receptor EP4 are less colitogenic. Absence of T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Our findings are further supported by a recent study demonstrating that PGE2 exacerbates TNF-induced inflammatory responses in human intestinal epithelial cells from patients with IBD who are resistant to TNF inhibitor therapy 46 . Moreover, recent studies including ourselves have suggested that lack of PGE2-EP4 signaling in T cells reduced both chemical-triggered acute and naïve T cell transfer-induced chronic intestinal inflammation, associated with reduction of inflammatory Th1 and/or Th17 cell responses 29,47,48 . This work thus advances our understanding that PGE2 mediates intestinal inflammation through modulating the network of the gut microbiota and the host immune system involving both innate MNPs and adaptive T cell responses.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings are further supported by a recent study demonstrating that PGE2 exacerbates TNF-induced inflammatory responses in human intestinal epithelial cells from patients with IBD who are resistant to TNF inhibitor therapy 46 . Moreover, recent studies including ourselves have suggested that lack of PGE2-EP4 signaling in T cells reduced both chemical-triggered acute and naïve T cell transfer-induced chronic intestinal inflammation, associated with reduction of inflammatory Th1 and/or Th17 cell responses 29,47,48 . This work thus advances our understanding that PGE2 mediates intestinal inflammation through modulating the network of the gut microbiota and the host immune system involving both innate MNPs and adaptive T cell responses.…”
Section: Discussionmentioning
confidence: 98%
“…Comparing the origin of PGE2 production in T‐cells with non‐lymphoid cells demonstrated that autocrine PGE2 production in T‐cells contributes to colitis, while paracrine PGE2 inhibits colon inflammation by favoring the expansion of T‐regulatory cells (Treg) cells. [ 87 ] Part of this variety of effects triggered by PGE2 is due to its four known receptors (EP1‐4), which exhibit different PGE2 binding affinities and have a range of tissue and cell‐specific expression patterns. [ 88 ] Similarly, prostaglandin D2 seems to modulate the neuro‐glio‐epithelial unit in two ways and seems to play a crucial role maintaining gut barrier integrity and inflammation in the gastrointestinal tract.…”
Section: Long‐chain N‐6 Eicosanoids and Inflammatory Bowel Diseasementioning
confidence: 99%
“…showed increased colonic PGE2 during T cell transfer colitis (35). Using a model of DSS colitis, we 5 observed a slight decrease of PGE2 during the acute inflammatory phase with a clear increase of PGE2 both in the colon and blood during the late phase of resolution of inflammation.…”
Section: Discussionmentioning
confidence: 70%